OR12-06 Nuclear Receptor CAR Protects Female Mice from the Development of Diet-Induced Nonalcoholic Fatty Liver Disease - Oliviero, Fabiana Layla (J Endocr Soc, 2020)
NAFLD (Non Alcoholic Fatty Liver Disease) has become the most common cause of chronic liver disease in many developed countries worldwide and represents a major health concern. The prevalence of NAFLD is sexually dimorphic with men suspected to be more susceptible to the development of hepatic steatosis than women. Women are mostly protected until hormonal imbalance induced by menopause. Nuclear receptor CAR (Constitutive Androstan Receptor) is at the crossroads between endocrine and metabolic regulations and could therefore represent an interesting therapeutic target. It is primarily expressed in the liver and involved in the catabolism of hormones such as thyroid hormones, corticosteroids and estrogens. In addition, several studies reveal a metabolic role of CAR through regulation of major hepatic pathways such as neoglucogenesis, beta-oxidation and de novo lipogenesis. Our research is aimed at better understanding the role of CAR using a mouse model genetically deficient for CAR. To explore the metabolic functions of CAR, knock-out male and female mice were subjected to a high fat diet (HFD) for 16 weeks. Concomitant CAR deletion and high fat diet induces sexually dimorphic metabolic disorders. Knock-out of CAR in males exacerbates HFD-induced fasted hyperglycemia whereas in females, it aggravates body weight gain and adipose tissue accumulation. In accordance with epidemiological studies revealing a protection of women from the development of hepatic steatosis, HFD-fed WT female mice present less important hepatic steatosis than HFD-fed WT male mice. However, following CAR deletion, HFD-fed female mice develop a severe steatosis along with important hepatic injury. Ongoing studies aim to understand the transcriptomic and endocrine dysregulations that may explain these phenotypes. These results reveal a previously unrecognized dimorphic role of CAR in energy homeostasis and highlights its involvement in the protection of female mice towards the development of hepatic steatosis. Overall, this research provides further insights in the pathogenesis of NAFLD and its dimorphic prevalence.